2004
DOI: 10.1590/s0073-47212004000100014
|View full text |Cite
|
Sign up to set email alerts
|

Dieta de espécies de Anostomidae (Teleostei, Characiformes) na área de influência do reservatório de Manso, Mato Grosso, Brasil

Abstract: ABSTRACT. Diet of Anostomidae species (Teleostei, Characiformes) in the influence area of Manso Reservoir, Mato Grosso, Brazil. The diet of four species of Anostomidae (Leporinus friderici Bloch, 1794, L. striatus Kner, 1858, L. elongatus Valenciennes, 1849 and Leporinus sp.) were investigated in the Manso Reservoir, Mato Grosso State, Brazil. Fish were sampled in three sites: upriver, in the main body of the reservoir, and below the dam. Were analized 276 stomachs. The diet was evaluated using the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
0
31
0
3
Order By: Relevance
“…Casatti et al 2005, Balassa et al 2004, Santos et al 2011). Resource partitioning is considered the principal factor in structuring the aquatic communities (Ross 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Casatti et al 2005, Balassa et al 2004, Santos et al 2011). Resource partitioning is considered the principal factor in structuring the aquatic communities (Ross 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed that the reproductive migration pattern of a host can be a determining factor in the composition and structure of parasite communities, as the short and long migrations performed by this species over its lifetime permit the fish to exploit diverse environments, increasing the possibility of infection/infestation by diverse species of parasites (Lizama et al 2006). Consequently, these divergent migratory characteristics may affect the endoparasite fauna, as related species usually exhibit divergent characteristics that make the coexistence possible (Dogiel 1961;Balassa et al 2004).…”
Section: Fauna Endoparasitária Dementioning
confidence: 99%
“…of the water), the filling phase of reservoirs has been marked by the ingestion of termites (Isoptera) that float on the water (Durães et al, 2001;Albrecht & Caramaschi, 2003a, b;Balassa et al, 2004). The differentiated morphology of the mouth seems to be a powerful mechanism that helps segregate species of Leporinus when several of them occur in the same environment, such as in the reservatório of Manso (Balassa et al, 2004).…”
Section: P R O O F Smentioning
confidence: 99%
“…The differentiated morphology of the mouth seems to be a powerful mechanism that helps segregate species of Leporinus when several of them occur in the same environment, such as in the reservatório of Manso (Balassa et al, 2004). The feeding activity of L. amblyrhynchus is considered discontinuous in view of the fluctuations verified in the capture of food during a daily cycle.…”
Section: P R O O F Smentioning
confidence: 99%